Antenatal depression and offspring health outcomes - Smith, Alexandra (Obstet Med, 2019)
BACKGROUND: Depression is the most common mental disorder during pregnancy, with prevalence rates between 4% and 20%. The objective of this review was to synthesize the literature on the association between antenatal depression and offspring birth outcomes, as well as developmental, behavioral, and psychiatric outcomes. METHODS: A search of PubMed, Cochrane, and Medline databases was conducted for articles published until December 2017. Articles focusing on the effects of antenatal depression on the offspring were selected to be reviewed. Reference lists of all studies were examined for any missed articles. A total of 32 articles were included in this review. RESULTS: Antenatal depression is associated with preterm birth, excessive infant crying, and offspring mental health problems. Untreated antenatal depression is strongly associated with adverse effects on the infant nervous system. CONCLUSION: Antenatal depression increases the likelihood of poor offspring health outcomes. Research should investigate whether medication use confounds this relationship.